立磨减速机弧齿锥齿轮副动态疲劳性能研究 - 张明 (Jixie chuandong)
The 3Dcontact finite element model of the input spiral bevel gear pair of vertical mill reducer is built,the flexible-body dynamics simulation analysis of bevel gear pair is carried out by using the LS-DYNA software,and the transient contact force is obtained,the fatigue life of the bevel gear pair is performed by using maximum main stress algorithm in FE-SAFE based on fatigue load spectrum,the S-N curve of the bevel gear pair and stress results of the bevel gear pair under static load.Then,the influence of stress concentration,loads and residual stress on fatigue life of bevel gear pair are studied based on the results above.The results indicate that the life decreases of bevel gear pair with the increase of stress concentration and loads,the fatigue life shows sensitization to loads,the residual tensile stress leads to a reduction of bevel gear pair fatigue life,however,the residual press stress leads to a increase of bevel gear pair fatigue life.